Preparation and analytical characterization of 1‐(1‐phenylcyclohexyl)piperidine (PCP) and 1‐(1‐phenylcyclohexyl)pyrrolidine (PCPy) analogues. Issue 7 (2nd April 2013) - Wallach, Jason; Paoli, Giorgia De; Adejare, Adeboye; Brandt, Simon D.; Brandt, Simon D.
<x xml:space="preserve">Abstract</x> Classic examples of psychoactive arylcycloalkylamines include ketamine and 1‐(1‐phenylcyclohexyl)piperidine (PCP) and many others serve as important structural templates for neuropharmacological research. The recent emergence of PCP analogues that can be obtained from internet retailers requires the implementation of appropriate monitoring strategies for harm reduction purposes. Access to analytical data plays a key part when encountering these substances, especially if reference material is not available. The present study describes the synthesis of three substituted 1‐(1‐phenylcyclohexyl)piperidines, (3‐MeO‐, 4‐MeO‐ and 3‐Me‐PCP) and three substituted 1‐(1‐phenylcyclohexyl)pyrrolidine analogues (3‐MeO‐, 4‐MeO‐ and 3‐Me‐PCPy). Analytical characterizations of all six arylcyclohexylamines and their primary 1‐phenylcyclohexanamine intermediates included gas chromatography ion trap electron‐ and chemical ionization and high resolution mass spectrometry, liquid chromatography electrospray hybrid triple‐quadrupole linear ion trap tandem mass spectrometry, infrared, diode array detection and 1H and 13C nuclear magnetic resonance (NMR) spectroscopy. Solvent (CDCl3 vs. d6‐DMSO) and protonation effects (free bases vs hydrochloride salts) were studied in order to investigate the impact on shifts and splitting patterns, for example, when attempting to assign separate axial and equatorial proton chemical shifts of NMR spectra. Differentiation between the isomeric 3‐MeO‐/4‐MeO‐PCP and PCPy analogues was feasible under mass spectral conditions. Gas chromatography analysis appeared to induce notable degradation of the 4‐MeO‐substituted analytes, especially when dealing with the HCl salts which led to the detection of the substituted 1‐phenylcyclohex‐1‐ene nucleus. This phenomenon was observed to be less pronounced with the 3‐MeO isomers, possibly due to the resonance properties of the para‐methoxy group followed by more facile elimination of the amine. Copyright © 2013 John Wiley & Sons, Ltd.